ANALISIS HIDROLOGI METODE HIDROGRAF SATUAN SINTETIS SNYDER UNTUK WILAYAH DAERAH ALIRAN SUNGAI TAYAN - Syarifah Melly Maulina; Ranty Christiana (Fakultas Teknik Universitas Panca Bhakti, 2022)
Tayan River is a tributary of the Kapuas watershed, which is located in Tayan Hilir District, Sanggau Regency, West Kalimantan. The wide-type watershed has tributaries that concentrate radially to a point so that large floods often occur at the meeting point of the tributaries. Therefore, it is necessary to conduct research on peak discharge analysis in the Tayan River watershed using the Synthetic Unit Hydrograph (HSS) Snyder approach. This research was conducted to determine the magnitude of the peak discharge in the Tayan River. The results showed the magnitude of the planned flood discharge using the Snyder method on the Tayan River in the periods of 2, 5, 10, 25, 50, 100, respectively, namely 221,608 m3/s, 311,221 m3/s, 363.441 m3/s, 435,545 m3/s, 489,568 m3/s and 543,747 m3/s..